2022
DOI: 10.3390/ijms231810924
|View full text |Cite
|
Sign up to set email alerts
|

Dual Mode of Mitochondrial ROS Action during Reprogramming to Pluripotency

Abstract: Essential changes in cell metabolism and redox signaling occur during the reprogramming of somatic cells into induced pluripotent stem cells (iPSCs). In this paper, using genetic and pharmacological approaches, we have investigated the role of electron transport chain (ETC) complex-I (CI) of mitochondria in the process of cell reprogramming to pluripotency. Knockdown of NADH-ubiquinone oxidoreductase core subunits S1 (Ndufs1) or subunit B10 (Ndufb10) of the CI or inhibition of this complex with rotenone during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 55 publications
3
12
0
Order By: Relevance
“…This deficit leads to the accumulation of ROS in mitochondria, which can cause damage to macromolecules and induce the release of ROS from the mitochondria into the cytosol, resulting in cellular senescence. 60,81,82 Consistent with these findings, our study showed that SOD2 expression was reduced and that cellular senescence was increased in BMSCs from mice fed an HFD. Conversely, increased SOD2 levels were observed in BMSCs treated with 1,25(OH) 2 D, accompanied by a reduction in BMSC senescence.…”
Section: Discussionsupporting
confidence: 87%
“…This deficit leads to the accumulation of ROS in mitochondria, which can cause damage to macromolecules and induce the release of ROS from the mitochondria into the cytosol, resulting in cellular senescence. 60,81,82 Consistent with these findings, our study showed that SOD2 expression was reduced and that cellular senescence was increased in BMSCs from mice fed an HFD. Conversely, increased SOD2 levels were observed in BMSCs treated with 1,25(OH) 2 D, accompanied by a reduction in BMSC senescence.…”
Section: Discussionsupporting
confidence: 87%
“…These results point to the association between NLI and long-term heart pathology because the decreased activity of the gene modules related to glutathione metabolism, metabolism of lipids, and aerobic respiration are well-known features of cardiovascular diseases and hypertension [ 74 , 98 , 114 ]. Moreover, it was indicated that the decreased activity of antioxidant system affects the cell differentiation state and can change the cell fate [ 115 , 116 , 117 ]. In accordance, glutathione deficiency was associated with structural cardiac abnormalities in patients with heart diseases and patients with still undetected cardiovascular pathologies, thus suggesting that a blood test including glutathione measuring can be used as a biomarker for asymptomatic cardiovascular disease detection [ 118 , 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the iPSCs reprogramming protocol, through viral transduction, is associated with high ROS generation, leading to oxidative damage, impaired cell survival, and increased genetic aberrations. Administration of AOX, such as NAC or vitamin C, improves reprogramming efficiency and reduces genetic abnormalities (Ji et al, 2014), thus validating the paradigm that also during the cell reprogramming, balanced levels of oxidative phosphorylation must be maintained on the route to pluripotency (Skvortsova et al, 2022). Telomere elongation is an iPSCs hallmark, thus the role of SIRTs in pluripotency maintenance has been extensively investigated.…”
Section: Sirts In Cellular Reprogrammingmentioning
confidence: 94%